Formulation of Instant Granule Containing Nano Calcium from the Shell of Freshwater Mussels (Anodonta woodiana) for Autism Children - Aminingsih, Tri; Srie Rahayu, Sata Yoshida; Yulianita, Yulianita (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
The small particle size of nano calcium from freshwater mussels shell will tend to increase the absorp- tion of calcium by humanâs body and will be very well consumed by children with special needs to suppress hyperactivity disorders that caused by mercury. This study aimed to create and determine the best instant granule formulation containing nano calcium from freshwater mussels shell. The research method began with the manufacture of freshwater mussels shell powder and isolated nano calcium. Nano calcium was tested for its solubility in acid. The granule formula was made with stevia varia- tions. Instant granule evaluation included granule ow test, rest angle, compressibility, water content, solubility, hedonic test, and calcium bioavailability. The results showed that nano calcium was soluble in 1:1 ratio of citric and tartrate acids, so that each formula needs 1.2% citric and 1.2% tartrate acids. Based on the avor, aroma, and texture, the most preferred granule formula contained 600 mg nano calcium, 60 mg citric acid, 60 mg tartaric acid, 400 mg stevia each sachet weighing 5 g. The best in- stant granule evaluation showed that the ow rate was 4.253 g/sec, 33.90 rest angle, 4.65% compress- ibility, 2.21% water content, soluble time 58 second and calcium bioavailability was 100%. Key words: Calcium bioavailability, detoxi cation, freshwater mussels, instant granule, nano cal- cium.